If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t(-16t + 8) = 0 Reorder the terms: t(8 + -16t) = 0 (8 * t + -16t * t) = 0 (8t + -16t2) = 0 Solving 8t + -16t2 = 0 Solving for variable 't'. Factor out the Greatest Common Factor (GCF), '8t'. 8t(1 + -2t) = 0 Ignore the factor 8.Subproblem 1
Set the factor 't' equal to zero and attempt to solve: Simplifying t = 0 Solving t = 0 Move all terms containing t to the left, all other terms to the right. Simplifying t = 0Subproblem 2
Set the factor '(1 + -2t)' equal to zero and attempt to solve: Simplifying 1 + -2t = 0 Solving 1 + -2t = 0 Move all terms containing t to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2t = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2t = 0 + -1 -2t = 0 + -1 Combine like terms: 0 + -1 = -1 -2t = -1 Divide each side by '-2'. t = 0.5 Simplifying t = 0.5Solution
t = {0, 0.5}
| 2(2.2b-1.6+b)=6.4 | | 5(1+8w)=10w+25 | | 8b+8=2(8p+4) | | -4y+8(4y+11)=36 | | 3(5x-4)=7x-12 | | 5/6×=-20 | | 3y-4=9y+32 | | 7v/4=49 | | q^2+1.4q-0.51=0 | | 52-x^2+10x=10 | | -9x+8x-5+2+2x= | | 102.5=2L+2W-11.75 | | 8t(-2t)=0 | | -4+8(4y+11)=36 | | -14x+18-11-2x+3= | | 3+2(1+5n)=65 | | 7.2(x-3.75)=-28.8 | | 6x-44*4x=22 | | 8x-2x+4=8 | | 5+2.50g=2.75 | | 12+48x+36y=528 | | 2x+2(0.25x)=5 | | 6v+3(-2v+5)=69 | | 6x-44*4x= | | 8-3x+7x-23= | | 3x+4.2=2q | | 13/4=x/12 | | 28x-35y=10 | | 52-x^2=10x | | (3/4)x-21/4 | | 2-5i/4-3i | | 38+4n=45.5+2.5n |